Dual-mobility cup total hip arthroplasty improves the quality of life compared to internal fixation in femoral neck fractures patients with severe neuromuscular disease in the lower extremity after stroke: a retrospective study - Liang, Chaolun; Chen, Bojian; Hu, Zhifeng; Li, Xing; Huang, Yongming (Frontiers in Surgery, 2023)
Background: We aimed to demonstrate that dual-mobility cup total hip arthroplasty (DMC-THA) can significantly improve the quality of life (QOL) of elderly femoral neck fracture patients with severe neuromuscular disease in unilateral lower extremities due to stroke compared to internal fixation (IF). Methods: From January 2015 to December 2020, we retrospectively examined 58 cases with muscle strength < grade 3/5 in the unilateral lower extremities due to stroke. Patients were separated into DMC and IF groups and the results were compared. The QOL was examined using the EQ-5D and SF-36 outcome measures. The physical and mental status was assessed using the Barthel Index (BI) and Fall Efficacy Scale-International (FES-I). Results: Patients in the DMC group had higher BI scores than in the IF group at different time point. Regarding mental status, the FES-I mean score was 42.1 ± 5.3 in the DMC group and 47.3 ± 5.6 in the IF group (p = 0.002). For the QOL, the mean SF-36 score was 46.1 ± 18.3 for the physical component score and 59.5 ± 15.0 for the mental component score compared to IF scores of 35.3 ± 16.2 (p = 0.035) and 46.6 ± 17.4 (p = 0.006). The mean EQ-5D-5L values were 0.733 ± 0.190 in DMC group and 0.303 ± 0.227 in the IF group (p = 0.035). Conclusion: We showed that DMC-THA significantly improved QOL compared to IF in elderly with femoral neck fractures and severe neuromuscular dysfunction in the lower extremity after stroke.